2018
DOI: 10.1097/md.0000000000013525
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal ablation of hepatic metastases from gastric adenocarcinoma on long-term survival

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A retrospective multicenter study from Japan found no significant difference in the survival between patients who underwent surgical resection and those who underwent local treatment, but also observed that patients staged as N0/N1 after the resection of their single metastatic and primary lesion had significantly better benefit from surgery or local treatment [ 210 ]. The results of a meta‐analysis showed that, compared with systemic chemotherapy, systemic chemotherapy combined with RFA in patients with liver metastasis (diameter <3 cm) could significantly prolong the survival time of these patients, with an mOS of 22.93 months [ 211 ]. d Krukenberg tumors are the metastatic lesion of gastric cancer that have been metastasized to the ovary.…”
Section: Comprehensive Treatment Of Gastric Cancermentioning
confidence: 99%
“…A retrospective multicenter study from Japan found no significant difference in the survival between patients who underwent surgical resection and those who underwent local treatment, but also observed that patients staged as N0/N1 after the resection of their single metastatic and primary lesion had significantly better benefit from surgery or local treatment [ 210 ]. The results of a meta‐analysis showed that, compared with systemic chemotherapy, systemic chemotherapy combined with RFA in patients with liver metastasis (diameter <3 cm) could significantly prolong the survival time of these patients, with an mOS of 22.93 months [ 211 ]. d Krukenberg tumors are the metastatic lesion of gastric cancer that have been metastasized to the ovary.…”
Section: Comprehensive Treatment Of Gastric Cancermentioning
confidence: 99%
“…Besides resection, other locoregional treatments such as radiofrequency ablation (RFA), microwave ablation (MWA) [ 16 ], hepatic artery infusion chemotherapy (HAIC) [ 17 ], transarterial chemoembolization (TACE) [ 18 ], and stereotactic body radiotherapy (SBRT) [ 19 ] have been investigated in mGC. Overall, these treatments were less invasive and associated with less minor and major complications, resulting at least non-inferior if compared to resection in highly-selected mGC patients with small (e.g., <3–5 cm in size for RFA and MWA) liver-limited lesions [ 16 ]. Of course, proper designed studies are warranted to better define the role of these treatments as potentially alternative or complementary to surgery and systemic treatment in selected mGC patients.…”
Section: Surgery and Locoregional Treatmentsmentioning
confidence: 99%
“…On the other hand, if surgery represents the cornerstone in the curative setting, its role in the metastatic disease is associated with controversial results [ 11 , 12 , 13 , 14 ] as well as the impact of other locoregional strategies [ 15 , 16 , 17 , 18 , 19 ]. In this regard, the concept of “oligometastatic” GC, stating a disease characterized by limited tumor burden (i.e., M1 with retroperitoneal lymph nodes and/or one potentially resectable incurable site), is taking place as emerging clinical entity, distinct from extensively mGC (M1 patients other than oligometastatic) in terms of both treatment plan (multimodal treatment vs. systemic treatment alone, respectively) and survival (mOS of about 31 months vs. 9–11 months, respectively) [ 12 , 13 , 14 , 15 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the largest series of MWA for LMGC (n=32), there was no recurrence at ablation site while 24 patients experienced recurrence at other than ablation site or extrahepatic sites (28). A recent systematic review and pooled analysis of RFA and MWA for LMGC (12 studies including 226 patients) showed that thermal ablative therapies may provide a survival benefit and should be considered an alternative option for the treatment of LMGC (64).…”
Section: Thermal Ablative Therapies As a Ldt Optionmentioning
confidence: 99%